Have Remittances Affected Real Unit Labor Costs in the Transition Economies of Eastern Europe, the South Caucasus, and Central Asia? - Okello, Jimmy Apaa; Brownbridge, Martin; Canagarajah, Sudharshan (World Bank, Washington, DC, 2021)
Twelve of the 29 transition economies in Europe and Central Asia are high remittance recipients, with average remittance receipts equivalent to 5 percent or more of their gross domestic product in the 2010s. The paper examines the evolution, during the 2000s and 2010s, of real unit labor costs, denominated in local currency and U.S. dollars, of the transition economies. Local currency and U.S. dollar real unit labor costs rose much faster between 2003 and 2015-17 in the high remittance recipient economies than in the other transition economies, although there was considerable variance between the countries in the high remittance recipient group. Among the high remittance recipients, approximately half of the increase in real unit labor costs denominated in U.S. dollars can be attributed to increases in local currency real unit labor costs and half to appreciation of their real exchange rates. Fixed effects and cross-country econometric estimates suggest that remittances had a positive and significant impact on the changes in domestic currency real unit labor costs in the transition economies.